DISAIN SISTEM INFORMASI PENDAFTARAN PASIEN BPJS RAWAT JALAN - Siti Nuryani (Jurnal Infokes, 2021)
The study aims to design and build a BPJS referral patient information system using Microsoft Visual Studio 2010 at the health center level. The research method used is a qualitative method with a descriptive approach. Data collection techniques used are through observation and literature studies. Software development methods use the waterfall method with Data Flow Diagram (DFD) as software design. From the results of the research conducted found the following problems: 1) Bpjs referral patient data processing still uses manual systems, 2) Record the report still uses Microsoft Excel,3)The input process has not worked properly due to lack of Human Resources. The advice given is: 1) Make the design of bpjs referral patient information system integrated at the same time can make reports effectively and efficiently, 2) Add Human Resources. Keywords: Design, Information System, Patient Referral Information System, BPJS.